A disappearing oasis in the semi-arid Chaco: Deficient palm regeneration and establishment - Puechagut, Patricia Beatriz (2012)
Palm forests of Copernicia alba are a rare habitat in the semi-arid Chaco of Northwestern Argentina, are centres of high species diversity, and provide key resources for many species. Our goal was to assess the conservation status of five C. alba patches in Northwestern Argentina: Reserve; Embarcación; Palma Sola; Vinalito; and, Talar. We compared patches to identify the sites with greatest conservation needs based on four criteria: population size structure; palm density (of individuals with height >1.30. m); probability of seedlings being browsed; and, presence of potential seed dispersers. We found that three (Embarcación, Reserve, and Talar) out of five sites had palm densities greater than 200 individuals/ha and only one site (Embarcación) showed a reverse J-shaped size structure for height. Reserve and Embarcación had the greatest probability of seedlings being browsed (0.99 ± 0.01 and 0.88 ± 0.12, respectively). A total of 14 potential disperser species of mammals and birds were recorded across the five sites. Only Reserve harboured all of the potential dispersers, but at least two potential disperser species were recorded at the other sites. None of the palm patches studied had an adequate conservation status. However, Embarcación met three out of four criteria, and therefore it can be considered to have the best conservation status in the semi-arid Chaco. Palma Sola and Vinalito have the greatest conservation needs. To conserve C. alba in Northwestern Argentina, strategies are needed that ensure seedling establishment for future populations to reach an adequate density and structure.